Is AI a Ghost Economic Agent? - Mancheva, Ivanina (Research Papers, 2025)
The invasion of artificial intelligence (AI) into economic and social life is leading to significant transformations. They raise the question of the role of AI in economic models and, in particular, whether it should be treated as an economic agent that makes independent decisions. This question, as well as the related problem of the legal capacity of AI, has not been answered. They are related to many topics discussed in recent years: the possibility of taxing robots, the liability of autonomous cars or the copyright of works created by AI. The study advocates a differentiated approach to defining AI as an independent economic agent. If answered in the affirmative, the key question would be what the the function that the AI maximizes and what are the constraints and risks that it faces. Although AI is still developing its capabilities and we do not have sufficient observations of the behavior of the most advanced systems, we assume that the more its independence from humans increases, the more it will become an economic agent.